Obesity Epidemiology, Pathogenesis, and Treatment 2014
DOI: 10.1201/b16443-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Adiposity Indicators for Predicting All-Cause Mortality in a Representative Sample of United States Non-Elderly Adults

Abstract: Background: Adiposity predicts health outcomes, but this relationship could depend on population characteristics and adiposity indicator employed. In a representative sample of 11,437 US adults (National Health and Nutrition Examination Survey, 1988-1994, ages 18-64) we estimated associations with all-cause mortality for body mass index (BMI) and four abdominal adiposity indicators (waist circumference [WC], waist-to-height ratio [WHtR], waist-to-hip ratio [WHR], and waistto-thigh ratio [WTR]). In a fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Recent studies on LAP have shown that LAP can be a powerful marker for detecting cardiometabolic risk factors. [2][3][4][5] Moreover the results of some studies indicate a correlation between higher LAP amounts and cardiovascular events in general populations 6,7 and also some subgroups. [8][9][10] Metabolically obese normal weight (MONW) is one of the most intriguing obesity phenotypes, which, despite normal BMI, seems to have greater risk of CVD in comparison with metabolically healthy obese phenotype (MHO).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on LAP have shown that LAP can be a powerful marker for detecting cardiometabolic risk factors. [2][3][4][5] Moreover the results of some studies indicate a correlation between higher LAP amounts and cardiovascular events in general populations 6,7 and also some subgroups. [8][9][10] Metabolically obese normal weight (MONW) is one of the most intriguing obesity phenotypes, which, despite normal BMI, seems to have greater risk of CVD in comparison with metabolically healthy obese phenotype (MHO).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, BMI is not a perfect measure of the degree of obesity, as theoretically, the effect of obesity on the body reflects the effect of adipose tissue on the body. Other measures that can determine the degree of obesity (adipose tissue) include waist circumference, waist–hip ratio, and visceral fat by cross-sectional imaging [ 28 , 29 ]. Future studies should explore the relationship of BMI with visceral fat as measured by anthropometric measurements or imaging or the impact of visceral fat alone in patients with CD and UC.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of age-related changes in LAP values in patients with hypertension indicates the early development of metabolic disorders manifested by the accumulation of lipids in the abdominal adipose tissue or an increase in the TG level in circulating blood. Only a limited number of population-based studies have estimated the effect of age on LAP values [13][14][15][16][17] . In addition, the designs of these studies varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be due to differences in sample populations with regard to age range, race/ethnicity, criteria for screening hypertension, and health status of the control group. Age seems to have the greatest impact on the optimal LAP cut-off points for predicting hypertension because of the effect of age on LAP values [13][14][15][16][17] .The aim of the study was to determine the age-adjusted optimal cut-off values of LAP for the prediction of hypertension risk.…”
mentioning
confidence: 99%